Thermoplastic Rubber (TPR) Modified by a Silane Coupling Agent and Its Influence on the Mechanical Properties of Oil Well Cement Pastes - Jianjian Song; Mingbiao Xu; Weihong Liu; Xiaoliang Wang; Peng Xu; Feng Huang; Yonggong Pan (Advances in Materials Science and Engineering)
The surface hydrophilicity of thermoplastic rubber (TPR) is poor, and the effect of using it directly in oil well cement is not good. TPR was modified by different silane coupling agents, and the hydrophilicity of the modified TPR was studied by Fourier-transform infrared (FT-IR) spectroscopy and dispersion stability photography. The application effect of modified TPR in oil well cement slurry was also evaluated. The fracture surface morphology of TPR cement stone was observed by macrophotography and scanning electron microscopy (SEM). The results demonstrated that the hydrophilicity of TPR particles was improved after modification with silane coupling agent 3-methacryloxypropyltrimethoxysilane (KH570), and its application effect in cement slurry was excellent. Compared with the pure cement paste, the compressive strength of the cement paste with addition of TPR modified by KH570 was reduced, but the flexural strength and impact strength of the cement paste were effectively enhanced. Moreover, the modified TPR greatly improved the deformation capacity and decreased the elastic modulus of the cement paste. The modified TPR particles formed a plastic polymer network structure in the cement stone and penetrated the cement hydration products, filling in the cement paste to form a flexible structural center. Thus, it improved the mechanical properties and reduced the brittleness of cement paste.